2014
DOI: 10.1186/1472-6920-14-137
|View full text |Cite
|
Sign up to set email alerts
|

Virtual patients: the influence of case design and teamwork on students’ perception and knowledge – a pilot study

Abstract: BackgroundVirtual patient (VP) cases are an effective teaching method, although little is known about how to design and implement them for maximum effectiveness. The aim of this study was to explore the effect of case design and teamwork on students’ learning outcome.MethodsOne hundred forty-six undergraduate medical students participated in a mandatory medical computer science course consisting of five seminars. At the end of each seminar, they worked on one VP case, either in teams of two or individually. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…pointed out that when learning basic concepts in PBL sessions, students and tutors were more appreciative of text than they were of multimedia content. As indicated by the findings, this is probably because of the fact that the use of multimedia (within VP sessions) impedes the possibility of fully exploring a problem and critically appraising the data since the focus in VP is more on patient management (from initial symptoms to patient treatment) and less on exploring the gaps in one's knowledge. This also plays into the findings of Jäger et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pointed out that when learning basic concepts in PBL sessions, students and tutors were more appreciative of text than they were of multimedia content. As indicated by the findings, this is probably because of the fact that the use of multimedia (within VP sessions) impedes the possibility of fully exploring a problem and critically appraising the data since the focus in VP is more on patient management (from initial symptoms to patient treatment) and less on exploring the gaps in one's knowledge. This also plays into the findings of Jäger et al .…”
Section: Discussionmentioning
confidence: 99%
“…This also plays into the findings of Jäger et al . who pointed out that students who worked in teams and had more clinical experience were also those who performed best in their post‐VP exams . Therefore, further research is needed to understand the best implementation of p‐PBL and VP in order to achieve the most effective teaching of core internal medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Jäger et al reported that brief VP cases, having a mean case study time of 15 min and important take-home messages in the design, were more effective on student outputs [38].…”
Section: Vp Designsmentioning
confidence: 99%
“…However, students prefer group work in terms of rectifying their deficiencies, increasing motivation and observing different approaches. Kühne-Eversmann submitted evidence that working with a partner activates the student, increases knowledge levels, improves reasoning abilities and elicits greater discussion about approaches to patient management [31,38,43]. Jäger et al revealed that students with high levels of preliminary knowledge who work with a partner are more successful and that short VP cases are more effective [38].…”
Section: Vp Designsmentioning
confidence: 99%
“…Written as branching narrative systems, VPs employ a wide set of patient-related data with which the learner interacts online and can practice their clinical decision making in a risk free environment (Ellaway et al, 2006). The data can be presented in multimedia formats, which enhance the learning experience (Jager et al, 2014). Virtual patients have been successfully integrated in medical and healthcare teaching for a number of years and are seen to offer advantages such as easy accessibility, reproducibility, interactivity, student autonomy and personalised feedback (Saleh, 2010).…”
Section: Introductionmentioning
confidence: 99%